THE TECHNOLOGY OF PERFORMING EXERCISES BY YOUNG GYMNASTS WITH OBJECTS (Scientific journal of the Fergana State University, 2024)
The presented article examines the characteristics of the standard of technique and the scale of errors for each element and determines their significance in the process of training young gymnasts at the stage of specialized training, which made it possible to agree on the opinion of experts and leading coaches of the republic. The targeted development of special motor training necessary for gymnasts to successfully work with apparatus has been determined. A classification of errors in the manipulation of objects made by gymnasts when performing exercises with them has been developed. In the process of research, shortcomings of the existing methodology for training gymnasts in the process of performing exercises with apparatus were identified.